Influence of role and competition stage on movement, heart rate and perceived task load characteristics of match officials during Men's and Women's Rugby League World Cup. - Johnson, Ella; Highton, Jamie; Twist, Craig (Journal of Sports Sciences, 2025)
We examined the influence of rugby league match officials' role and competition stage on movement, heart rate and subjective task loads during international competition. Measures were recorded from all 28 match officials (male n = 25; female n = 3; 4 ± 3 matches per official) comprising 42 referees and 84 touch judge performances from Men's (n = 29) and Women's (n = 13) World Cup matches. More accelerations (p = 0.003) and decelerations (p = 0.013), higher mean heart rates (p = 0.006) and perceived physical load (p < 0.001) and less high-speed running (p = 0.002) occured in referees compared to touch judges. Distance, high-speed running, accelerations/decelerations, heart rate, and subjective mental, physical, temporal, effort and frustration loads (all p < 0.05) were higher during the Men's compared to Women's competition. Mean speed and high-speed running (all p < 0.05) decreased between halves in the Knockout stage, while subjective mental, physical, temporal and effort load increased (all p < 0.05). Declines in relative high-speed running between the halves were also greater during the Knockout stage (p = 0.016). The on-field role, the competition and stage influence the physical, heart rate and perceived task loads of rugby league match officials.